2021
DOI: 10.1038/s41467-021-26071-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally blue hydrated parent body of asteroid (162173) Ryugu

Abstract: Ryugu is a carbonaceous rubble-pile asteroid visited by the Hayabusa2 spacecraft. Small rubble pile asteroids record the thermal evolution of their much larger parent bodies. However, recent space weathering and/or solar heating create ambiguities between the uppermost layer observable by remote-sensing and the pristine material from the parent body. Hayabusa2 remote-sensing observations find that on the asteroid (162173) Ryugu both north and south pole regions preserve the material least processed by space we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…We do note, however, that measurements by Tatsumi et al (2021) point to the possibility that Ryugu has both ST and NST material; the boulder Otohime Saxum is reported to have a deeper 0.7 μm band on one facet than on other facets or on Ryugu as a whole, and interestingly, NIRS3 spectra of that same facet show a more ST-like band shape near 3 μm than is seen in other Ryugu spectra. However, interpretations are confounded by the relatively large absolute uncertainties on absolute 0.7 μm BD in the Hayabusa2 data.…”
Section: Do Objects Have Both St and Nst Spectra On Theirmentioning
confidence: 63%
See 1 more Smart Citation
“…We do note, however, that measurements by Tatsumi et al (2021) point to the possibility that Ryugu has both ST and NST material; the boulder Otohime Saxum is reported to have a deeper 0.7 μm band on one facet than on other facets or on Ryugu as a whole, and interestingly, NIRS3 spectra of that same facet show a more ST-like band shape near 3 μm than is seen in other Ryugu spectra. However, interpretations are confounded by the relatively large absolute uncertainties on absolute 0.7 μm BD in the Hayabusa2 data.…”
Section: Do Objects Have Both St and Nst Spectra On Theirmentioning
confidence: 63%
“…If, conversely, Bennu and Ryugu are thought likely to have originated as part of the same object after sample analysis, many of the scenarios considered in Section 5 will need to be revised or discarded. We note that, from geophysical data, Tatsumi et al (2021) could not rule out that Bennu and Ryugu could represent the same parent body, but based on space weathering trends, as well as a difference in the 2.7 μm BD, they suggested that is a "lower possibility. "…”
Section: Ryugu and Bennumentioning
confidence: 88%
“…Thus, the observed change of spectral slope and absorption band in reflectance spectra of C-type asteroids compared with carbonaceous chondrites meteorites is difficult to interpret [15][16][17][18][19][20] . JAXA's Hayabusa2 spacecraft observed spectral variation on asteroid Ryugu [21][22][23][24] thought to be related to space weathering. Our studies of Ryugu samples offer the first opportunity to directly link the spectral variation to the space-weathering-induced physical and chemical alteration of regolith on C-type asteroids.…”
mentioning
confidence: 99%
“…In addition to the mass-shedding process on the surface of Ryugu, the pole stability may contribute to the formation of the latitudinal pattern in the visible and near-infrared spectra (Sugita et al, 2019). This may have protected the polar regions from sunlight and maintained their bluer spectra, which is consistent with the distribution of fresh materials least processed by space weathering (Tatsumi et al, 2021).…”
Section: Implications For Geologic History Of Ryugumentioning
confidence: 73%